Modern chromatographic analysis of vitamins - Leenheer, André P. De (Marcel Dekker, 2011)
Containing over 1450 references, drawings, and tables that elaborate on the determination of vitamins in different matrices, the Third Edition of Modern Chromatographic Analysis of Vitamins contains chromatographic data on all vitamins in one volume ... extends and adds sections on capillary electrophoresis and mass spectrometry ... updates and revises material on metabolism and biological function ... provides guidance in conducting state-of-the-art separation analyses ... details the latest extraction procedures ... includes an enlarged and comprehensive subject index ... and much more.